2014
DOI: 10.1016/j.jaci.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated dissociation of IgE-FcεRI complexes by disruptive inhibitors actively desensitizes allergic effector cells

Abstract: Background The remarkably stable interaction of immunoglobulin E (IgE) with its high-affinity receptor FcεRI on basophils and mast cells is critical for the induction of allergic hypersensitivity reactions. Due to the exceptionally slow dissociation rate of IgE:FcεRI complexes such allergic effector cells permanently display allergen-specific IgE on their surface and immediately respond to allergen challenge by releasing inflammatory mediators. We have recently described a novel macromolecular inhibitor that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(124 citation statements)
references
References 45 publications
5
114
0
2
Order By: Relevance
“…Eggel et al [24] in their study revealed that omalizumab not only neutralizes free IgE and decreases expression but also might accelerate dissociation of IgE from FceRI on basophils. This observation was confirmed by Serrano-Candelas et al [25] on mast cells.…”
Section: Pharmacodynamic Properties Of Omalizumabmentioning
confidence: 97%
“…Eggel et al [24] in their study revealed that omalizumab not only neutralizes free IgE and decreases expression but also might accelerate dissociation of IgE from FceRI on basophils. This observation was confirmed by Serrano-Candelas et al [25] on mast cells.…”
Section: Pharmacodynamic Properties Of Omalizumabmentioning
confidence: 97%
“…164 In a recent study, treatment with a novel DARPin (E2_79) rapidly disrupted IgE-FcεRI complexes on the surface of basophils and blocked IgE-dependent responses in a humanized mouse model of passive anaphylaxis. 165 In the same study, treatment with a bivalent DARPin (bi53_79), or two DARPins fused together, was more efficacious in reducing anaphylaxis than omalizumab. While studies of DARPins in the treatment of allergy are in their infancy, and future clinical trials are needed to test their safety and efficacy, these disruptive IgE inhibitors may be ideal therapeutics due to their potency and potential to reduce allergic symptoms.…”
Section: Ige Pathway Targetsmentioning
confidence: 97%
“…Peptidebased mimicry of IgE or FcεRI components can disrupt the interaction between IgE and its receptor, but the bioavailability and pharmacokinetic characteristics of peptides are not optimal and they are some ways from clinical testing (Eggel et al, 2014;Zhou et al, 2013). Monoclonal antibodies, including omalizumab, have shown promise (Logsdon & Oettgen, 2015).…”
Section: Silencing Of the Ige: Mast Cell Axis To Restore Immune Homeomentioning
confidence: 99%